2019
DOI: 10.1002/chem.201905177
|View full text |Cite
|
Sign up to set email alerts
|

N‐Heterocyclic Carbene‐Catalyzed Formal [6+2] Annulation Reaction via Cross‐Conjugated Aza‐Trienolate Intermediates

Abstract: The diverser eactivity of N-heterocyclic carbenes (NHCs) in organocatalysis is due to the possibility of different modeso fa ction. Although NHC-bounde nolates and dienolates are known, the related NHC-bound cross-conjugated aza-trienolates remain elusive. Herein,w ed emonstrate the NHC-catalyzed formal [6+ +2] annulation of nitrogen-containing heterocyclic aldehydes with a,a,a-trifluoroacetophenones leadingt ot he formation of versatile pyrrolooxazolones (29 examples). The catalytically generated cross-conjug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…A short time later, Biju, 9 Hui 10 and co-workers independently reported similar transformations to this protocol. DFT studies towards the NHC-catalyzed aromatic N activation mechanism and additional electrophile investigations are provided in their studies.…”
Section: Covalent Activation Of Nitrogen Atomsmentioning
confidence: 75%
“…A short time later, Biju, 9 Hui 10 and co-workers independently reported similar transformations to this protocol. DFT studies towards the NHC-catalyzed aromatic N activation mechanism and additional electrophile investigations are provided in their studies.…”
Section: Covalent Activation Of Nitrogen Atomsmentioning
confidence: 75%
“… [8a] In the same year we found that addition of a carbene catalyst to indole aldehydes at a remote site could enable an asymmetric NH functionalization [8b] . Very recently, independent studies reported by Biju, [9a] Hui [9b] and us [9c] showed that under the catalysis of NHCs the N ‐centered nucleophiles could be functionalized via the formation of aza ‐fulvene intermediates (Figure 1 a). In all these NHC‐catalyzed asymmetric functionalizations of heteroatoms (Figure 1 a), the reactive nucleophilic heteroatoms are at the γ‐position relative to the carbonyl moieties of the substrates.…”
Section: Introductionmentioning
confidence: 76%
“…In close analogy to the works built around NHC‐bound aza ‐ o ‐QM [116] and aza ‐fulvene intermediates, [118–120] both isatins (Scheme 82A) and acyclic ketones (Scheme 82B) have succeeded in reacting with the imines derived from 2‐amino(benz)imidazoles in a highly enantioselective fashion, giving a very broad range of polynitrogenated heterocyclic products (40–98 % yield, 72–98 % ee), and beyond that, inexpensive MnO 2 could be used in lieu of DQ oxidant without any detrimental impact on yields and/or selectivities.…”
Section: Nhc‐bound Ortho‐quinone Methide Aza‐fulvene and Triaza‐diene...mentioning
confidence: 98%